Taller de intervención y erradicación de la deserción escolar para disminuir los efectos psico-sociales en la escuela fiscal mixta “ciudad de Machachi” en el periodo académico 2012-2013 - Guerrero Barros, Mirian Rocio (2013)
CurriculumUpdating andstrengthening oftheBasic General Educationin our countryis partof theconsensus processofsocialreform.This allows the constructionofa real society anda modern,efficientand based onthe common good,onthe basis oftrainingcomprehensivehuman beings.All this workis framed bythe need to contributetosolve or reduce thedropoutrate ofchildren. Theyfacethis problemand improvetheir chances of successin their studies andin theirpresent and future lives. The followingresearch aims, supportparents andteachersthat allefforts will beansweredin each oftheboys and girls will bethe mainbeneficiariesbecause they will havehighself -esteemand feelsupported by their familiesandsociety in general. Therefore itoffers a new perspectiveof success andwell-being. These will not onlystudents andtheir families. Itgoesbeyondthereachtheentirecommunity.